DEVELOPMENT OF FLASHCARD MEDIA TO TEACH STUDENTS' VOCABULARY MASTERY IN READING SKILL AT TAHFIDZUL QUR'AN ISLAMIC BOARDING SCHOOL ANNUR ALHIDAYAH - Cindi Ulfatus Sahrani; Siti Rofi’ah; Ahmad Saifudin (UIBU, 2023)
This study aims to develop Flashcard learning media in learning English vocabulary mastery at the Tahfidzul Qur'an Annur Alhidayah Islamic Boarding School. The research method used is research and development with the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, and questionnaires. Data analysis is carried out using qualitative data analysis and quantitative data analysis. The result of this study is a revised Flashcard media based on advice from media experts. The revision of the Flashcard media includes the addition of adjectives and verbs as new forms and types of words. Product trials were carried out in English course classes at the Tahfidzul Qur'an Annur Alhidayah Islamic Boarding School. The results of the trial showed that the use of Flashcard media can improve students' vocabulary mastery. The study also compared with previous studies that used vocabulary learning strategies without expert assistance. In conclusion, the development of this Flashcard media can be an effective alternative in learning English vocabulary mastery at the Tahfidzul Qur'an Annur Alhidayah Islamic Boarding School